Teknik produksi dan pemasaran Batik Parang Kaliurang - Rianto, Rianto; Setyawati, Endang; Wahyuhana, Ratika Tulus; Setiafindari, Widya (Institut Teknologi Dirgantara Adisutjipto, 2023)
Batik Parang Kaliurang is a women's business group located in South Kaliurang, Sleman,Yogyakarta. Batik Parang Kaliurang existed until 2020, marked by many orders from within and outside the country. Several marketing support activities have also been followed, such as participating in exhibitions, competitions, training, and other activities. Conditions changed when the COVID-19 pandemic occurred with several government regulations to break the chain of virus spread, one of which was social distancing. The impact of this regulation is the lack of visitors to the showroom so that from 2020 to 2021, Parang Kaliurang batik will almost not produce. This is partly because Parang Kaliurang batik does not have media for product marketing or digital exhibitions. This community service aims to regenerate transactions in Parang Kaliurang batik by expanding the marketing network through cyberspace. However, this facility is also not accessible because of several obstacles such as production space and the ability of human resources to operate technology.